Transnational solidarity : concept, challenges and opportunities / edited by Helle Krunke, Hanne Petersen, Ian Manners. - Krunke, Helle, 1970-; Petersen, Hanne, 1951-; Manners, Ian (Cambridge University Press, 2020)
The book analyses the concept and conditions of transnational solidarity, its challenges and opportunities, drawing on diverse disciplines as Law, Political Science, Sociology, Philosophy, Psychology and History. In the contemporary world, we see two major opposing trends. The first involves nationalistic and populistic movements. Transnational solidarity has been under pressure for a decade because of, among others, global economic and migration crises, leading to populistic and authoritarian leadership in some European countries, the United States and Brazil. Countries withdraw from international commitments on climate, trade and refugees and the European Union struggles with Brexit. The second trend, partly a reaction to the first, is a strengthened transnational grass-root community - a cosmopolitan movement - which protests primarily against climate change. Based on interdisciplinary reflections on the concept of transnational solidarity, its challenges and opportunities are analysed, drawing on Europe as a focal case study for a broader, global perspective.